Using Artificial Intelligence to Advance Public Health - Weeks, Bill; Taliesin, Brian; Lavista Ferres, Juan M. (International Journal of Public Health (IJPH), 2023)
Artificial intelligence (AI) and its application to healthcare has captured the imagination of the media, particularly since the release of Generative Pre-trained Transformer (GPT) large language models in late 2022. In the medical literature, application of AI to medicine and clinical care has been more tempered, balanced, and long-lived, with exponential growth in the number of PubMed results over the past 20 years. AI has seemingly become integral to the future of healthcare, with the National Academy of Medicine embracing AI as part of a more agile future of medicine, the New England Journal of Medicine introducing a new series and journal dedicated to the topic, and the World Health Organization releasing guidance on its ethical use and governance.